Monitoring Manajemen Irigasi Pada Budidaya Melon Berbasis IoT - Fadli Irsyad; Khairil Agustoria (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2026)
Uncertainty in irrigation water supply in agricultural land is often one of the main factors causing a decline in crop production capacity. Manual irrigation not only requires additional labor but also consumes considerable time, thereby reducing farmers’ work efficiency. Therefore, innovations are needed in the form of a more modern, efficient irrigation system capable of adjusting to crop requirements in real time. The main objective of this study is to develop a drip irrigation monitoring and control system based on the Internet of Things (IoT) to meet the water and nutrient needs of melon plants. The designed system utilizes a capacitive soil moisture sensor, a soil pH sensor, and a DHT-22 temperature and humidity sensor. All sensors are connected to an ESP32 microcontroller, which processes the data and automatically transmits it to a spreadsheet application for recording and monitoring purposes. The fertigation system has dimensions of 510 × 150 cm and applies drip irrigation technology controlled automatically based on soil moisture and soil acidity (pH) values. The results of the correlation analysis showed that the average coefficients of determination (R²) for the soil moisture sensor, soil pH sensor, and DHT-22 sensor were 0.8395, 0.9896, and 0.984, respectively. Plant observations indicated that the average plant height in the automated system was 48.19 cm, which was higher than the control plants at 43.69 cm. Thus, the IoT-based fertigation system proved to operate effectively, more efficiently, and with better performance compared to conventional methods.